PENGARUH AKSES KEUANGAN TERHADAP PERTUMBUHAN UKM DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI - Geriadi, Made Ayu Desy; Erynayati, Luh; Ria Sawitri, Ni Putu Yuliana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This examination means to decide how the role financial literacy in moderating the relationship of access to finance and growth. The area for this exploration held in Denpasar. The quantity of tests taken is 100 small medium enterprise (SMEs), with a likelihood inspecting methods are basic irregular examining. Information examination in this investigation utilized the Partial Least Square (PLS) approach. PLS is a condition model for Structural Equation Modeling (SEM) in view of parts or variations. This examination is to get results which expressed that the access to finance has a positive and significant effect on growth of SMEs. Financial literacy has a positive and significant effect on growth of SMEs. Financial literacy moderates the relationship between access to finance and growth of SMEs